Serum prolactin for differentiating epileptic seizures in children - Harry Mangunsong (Paediatrica Indonesiana, 2015)
Background Serum prolactin level has been used as a marker to differentiate epileptic from non-epileptic seizures in adults. Electroencephalogram (EEG) examination is the primary diagnostic tool used to assess seizures. However, EEGs are quite difficult to perform in children and have sensitivity of only 50%- 55%, with 96% specificity. Objective To assess the diagnostic potential of serum prolactin level as an alternative tool for children for differentiating between epileptic and non-epileptic seizures. Methods This diagnostic study was performed between January 2013 and December 2013. Thirty patients aged 3 months to 15 years with seizures and without fever who visited the Emergency Department of Arifin Ahmad Hospital, Pekanbaru, Riau, were included. Blood specimens were collected within 2 hours after seizure. Subjects underwent serum prolactin measurements and EEG examinations. Results Fifteen subjects had normal EEGs and 15 subjects had abnormal EEGs. Post-ictal serum prolactin levels were significantly higher in the epileptiform EEG group. The mean serum prolactin levels were 23.78 (SD 21.86) ng/mL and 10.57 (SD 5.62)ng/mL in patients with epileptic and non-epileptic patients, respectively. Using a prolactin cut-off point of 17.2 ng/mL, serum prolactin had a 73.3% sensitivity and 93.3% specificity for differentiating between epileptic and non-epileptic seizures. Conclusion Our findings suggest that serum prolactin level increases after an epileptic seizure, but not after a non-epileptic seizure. Post-ictal prolactin elevation within 2 hours may be useful in differentiating epileptic seizures from non-epileptic seizures.